Unveiling the significance of prokaryotic composition from ferromanganese crusts regarding the interlink between cobalt and vitamin B12 in deep-sea ecosystems - Montoya, Lilia; Escobar-Briones, Elva (Frontiers in Microbiology, 2025)
The intricate relationship between prokaryotic vitamin B12 (cobalamin) producers and metazoans in deep-sea ecosystems, particularly within ferromanganese crusts and polymetallic nodules, is critical for understanding oceanic biogeochemical cycling of cobalt. Microbial communities are key regulators of essential biogeochemical cycles, with cobalt serving as a vital component in the synthesis of cobalamin, a metallocofactor indispensable for numerous metabolic processes. We analyzed the significance of cobalamin biosynthetic pathways confined to prokaryotes and emphasized the ecological importance of auxotrophic organisms that rely on exogenous sources of vitamin B12. Additionally, we recognize recent research regarding the spatial distribution of dissolved cobalt and its consequential effects on cobalamin production and bioavailability, indicating the scarcity of cobalt and cobalamin in marine environments. We propose that cobalt-rich environments may foster unique interactions between prokaryotic and eukaryotic organisms, potentially altering the food web dynamics owing to the localized abundance of this element. By investigating the roles of cobalt and cobalamin in nutrient cycling and interspecies interactions, we outlined key criteria for future research on deep-sea microbial communities and their contributions to the cobalt biogeochemical cycle.